Anti-tumour activity of zinc ionophore pyrithione in human ovarian cancer cells through inhibition of proliferation and migration and promotion of lysosome-mitochondrial apoptosis - Mengge Chen; Yanpeng Ding; Yuan Ke; Yifei Zeng; Nuomin Liu; Yahua Zhong; Xinying Hua; Zheng Li; Yudi Xiong; Chaoyan Wu; Haijun Yu (Artificial Cells, Nanomedicine, and Biotechnology)
Zinc pyrithione (ZPT) is widely used as an antimicrobial. Zinc is a necessary trace element of the human whose homeostasis associated with several cancers. However, the anticancer effect of increased Zinc in ovarian cancer is still unclear. This study focussed on the anti-tumour effects of ZPT combined with Zinc in SKOV3 and SKOV3/DDP cells. The cell viability, apoptosis, migration, and invasion assays were detected by CCK-8, flow cytometry, wound healing and transwell assay, respectively. The distribution of Zinc in cells was monitored by staining of Zinc fluorescent dye and lysosome tracker. The changes in lysosomal membrane stability were reflected by acridine orange fluorescence and cathepsin D reposition. Expression of the proteins about invasion and apoptosis was evaluated by western blot. The results indicated that ZPT combined with Zinc could notably reduce cell viability, inhibit migration and invasion in SKOV3 and SKOV3/DDP cells. Besides, ZPT performed as a Zinc carrier targeted lysosomes, caused the increase of its membrane permeability and the release of cathepsin D accompanied by mitochondrial apoptosis in SKOV3/DDP cells. In conclusion, our work suggests that ZPT combined with Zinc could inhibit proliferation, migration, invasion, and promote apoptosis by trigger the lysosome-mitochondrial apoptosis pathway in ovarian carcinoma.